2005
DOI: 10.1021/bi051714v
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of MKK6-Dependent Activation by Binding to p38α MAP Kinase

Abstract: Inhibition of p38alpha MAP kinase is a potential approach for the treatment of inflammatory disorders. MKK6-dependent phosphorylation on the activation loop of p38alpha increases its catalytic activity and affinity for ATP. An inhibitor, BIRB796, binds at a site used by the purine moiety of ATP and extends into a "selectivity pocket", which is not used by ATP. It displaces the Asp168-Phe169-Gly170 motif at the start of the activation loop, promoting a "DFG-out" conformation. Some other inhibitors bind only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 45 publications
(92 reference statements)
5
78
0
Order By: Relevance
“…3 shows that the local conformation of the DFG motif in the AMD computed pseudo-DFGout conformation is different from the a-DFG-out conformations found in the mutants F169G and F169R described by Bukhtiyarova et al, 18 and from the DFG-'in between' conformation found in some crystal complexes, [19][20][21]10 where the / angle is in the range À60°to À70°and the w is in the range À25°to À55°. The portion of the DFG loop at the N-terminal side of the DFG motive is not completely resolved in these crystal structures, however, a visual inspection of the resolved chain segments reveals that in all the structures the loop is prone to assume a conformation which is very similar among the crystal structures but very different from the AMD pseudo-DFG-out.…”
Section: Structural Analysis: the Pseudo-dfg-out Conformationmentioning
confidence: 76%
See 1 more Smart Citation
“…3 shows that the local conformation of the DFG motif in the AMD computed pseudo-DFGout conformation is different from the a-DFG-out conformations found in the mutants F169G and F169R described by Bukhtiyarova et al, 18 and from the DFG-'in between' conformation found in some crystal complexes, [19][20][21]10 where the / angle is in the range À60°to À70°and the w is in the range À25°to À55°. The portion of the DFG loop at the N-terminal side of the DFG motive is not completely resolved in these crystal structures, however, a visual inspection of the resolved chain segments reveals that in all the structures the loop is prone to assume a conformation which is very similar among the crystal structures but very different from the AMD pseudo-DFG-out.…”
Section: Structural Analysis: the Pseudo-dfg-out Conformationmentioning
confidence: 76%
“…Similar intermediate conformations, also named DFG-'in between', were found depending on the structure of the ligands co-crystallized with the p38a proteins manipulated in positions different from the DFG-motive and under different crystallization conditions. [19][20][21]10 In summary, two mechanisms have been up to now envisaged in the literature for allosteric inhibitors: (1) exclusively binding to proteins in the DFG-out conformation, which, although sampled less frequently, exists in equilibrium with the DFG-in conformation; (2) initial binding to proteins in the DFG-in conformation with subsequent promotion of the DFG-in to -out transition. Besides the recent evidences brought to support this second thesis, no description of the mechanism at the atomic level has yet produced.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic data generated during the discovery of BIRB-796 established the slow binding kinetics of DFG-out inhibitors 7 and also highlighted that some allosteric inhibitors can display the ability to induce a conformation in which both the activated enzyme can be potently inhibited and the unphosphorylated enzyme can not be activated by phosphorylation on the activation loop. 30 …”
Section: Introductionmentioning
confidence: 99%
“…However, because the concentration response relationship for binding to the non-activating kinase is the same as that for test compound binding to the upstream activating kinase, ITC offers a simpler assay format for measuring affinities. Examples from our work include MEK protein kinase and p38a MAP kinase (VanScyoc et al, 2008;Sullivan et al, 2005).…”
Section: Thermodynamic Methods -Itcmentioning
confidence: 99%